2012
DOI: 10.3892/ijo.2012.1647
|View full text |Cite
|
Sign up to set email alerts
|

Circulating microRNAs: New biomarkers in diagnosis, prognosis and treatment of cancer (Review)

Abstract: Abstract. MicroRNAs (miRNAs) are small non-coding, endogenous, single-stranded RNAs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
208
0
10

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 321 publications
(225 citation statements)
references
References 199 publications
2
208
0
10
Order By: Relevance
“…Blood-based miRNA profiling is not as reliable as tissue-based miRNA-profiling, but offers the potential for early, non-invasive, sensitive and specific cervical cancer detection and screening. Recently, several circulating miRNAs have been identified as potential serum biomarkers in different cancer types (19). These serum miRNAs may be effective as predictive biomarkers in cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Blood-based miRNA profiling is not as reliable as tissue-based miRNA-profiling, but offers the potential for early, non-invasive, sensitive and specific cervical cancer detection and screening. Recently, several circulating miRNAs have been identified as potential serum biomarkers in different cancer types (19). These serum miRNAs may be effective as predictive biomarkers in cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, many studies have shown that miRNAs are stable in blood samples, thus, making the quantitative detection of miRNAs in blood feasible. Therefore, miRNAs in blood have been extensively studied as biomarkers for GC diagnosis, prognosis and treatment (20)(21)(22)(23)), yet, specific circulating miRNAs associated with distant metastasis in GC remain unidentified. The aim of the present study was to identify specific miRNAs in GC/DM plasma samples.…”
Section: Introductionmentioning
confidence: 99%
“…These noncoding RNAs function by regulating gene expression through mRNA degradation or the inhibition of protein translation (1,2) and are dysregulated in all cancers (3). Interestingly, miRNAs have also recently been discovered extracellularly, contained in body fluids such as serum, plasma, urine, milk, and spinal fluid (4)(5)(6)(7). These circulating miRNAs are embedded in microvesicles (MVs)/exosomes, which are small, membrane-derived particles, usually 30 nm to 1 μm in size (8).…”
mentioning
confidence: 99%